Peran Manajemen Sumber Daya Manusia Syariah dalam Menciptakan Lingkungan Kerja yang Berkeadilan - Pratami, Marissa Zahra (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Human Resource Management involves the study of overseeing the interactions and responsiibilities of employees to ensure effectiveness and efficiency in reaching the organization’s objectives or vision. In the concept of sharia, Human Resource Management uses Islamic principles, namely the principle of trust, the principle of syirkah, the principle of cooperation in goodness, the principle of social responsibility, the principle of joint ownership, the principle of economic distribution, and the principle of justice. The creation of fair Sharia Human Resource Management in the work environment, it is necessary to pay attention to employee performance, work environment, organizational culture, and organizational justice. The author in this study aims to analyze the role of sharia human resource management in creating an equitable work environment. The method used by the author is literature review by involving 29  data sources that are in accordance with the research topic. The results of this study indicate that sharia principles in economic activities, especially in Human Resource Management can create justice in the work environment. Employees as Human Resources are a central and important sector because they will support the achievement of the company's vision, so employee performance, work environment, organizational culture, and fairness to employees must be considered and become a priority for the company. The conclusion of this research is that Sharia Human Resources with principles that prioritize truthfulness, trustworthiness, and so on can support the occurrence of a fair work environment.